RANCANG BANGUN PEMBUATAN MESIN PENCACAH SAMPAH PLASTIK MINIMALIS - Erlina Prasetyawati; Sabdho Kencono; Joko Suparno; Yuliarto Joko Sumbogo; Ardiansyah, Dimas; Gnemon Isvandianto Surya Rajasa (Accurate: Journal of Mechanical Engineering and Science, 2024)
A plastic waste shredder is a tool used to shred or crush plastic into small pieces using a cutting knife mounted on a shaft connected via a pulley and belt transmission to a motor. This study is an experimental study to design a waste shredder with a more minimalist design that uses a 1000 RPM washing machine dryer dynamo drive motor, but aims to be able to participate in overcoming the current plastic waste problem. The results of the study showed that this machine with a 1000 RPM washing machine dynamo drive motor can only crush PET plastic beverage bottle waste that must be cut into pieces first to avoid stopping the machine and slipping material. Based on these results, it can be concluded that this machine is only intended for shredding thin PET plastic bottles.